2020
DOI: 10.1016/j.ebiom.2020.102919
|View full text |Cite
|
Sign up to set email alerts
|

Microglia facilitate loss of perineuronal nets in the Alzheimer's disease brain

Abstract: Background Microglia, the brain's principal immune cell, are increasingly implicated in Alzheimer's disease (AD), but the molecular interfaces through which these cells contribute to amyloid beta (Aβ)-related neurodegeneration are unclear. We recently identified microglial contributions to the homeostatic and disease-associated modulation of perineuronal nets (PNNs), extracellular matrix structures that enwrap and stabilize neuronal synapses, but whether PNNs are altered in AD remains controversia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
152
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(162 citation statements)
references
References 88 publications
9
152
1
Order By: Relevance
“…Recent studies have identified a novel contribution of microglia in modulating perineuronal nets (PNNs) in the adult brain 60, 61 , specialized extracellular matrix assemblies that enwrap neurons and proximal dendrites to regulate synaptic plasticity 62 , protect against neurotoxins 63 , and enhance signal propagation 60, 61 , among other functions. In control brains, PNNs (as detected by Wisteria floribunda agglutinin (WFA) staining) are preferentially found on parvalbumin (PV) expressing cells.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have identified a novel contribution of microglia in modulating perineuronal nets (PNNs) in the adult brain 60, 61 , specialized extracellular matrix assemblies that enwrap neurons and proximal dendrites to regulate synaptic plasticity 62 , protect against neurotoxins 63 , and enhance signal propagation 60, 61 , among other functions. In control brains, PNNs (as detected by Wisteria floribunda agglutinin (WFA) staining) are preferentially found on parvalbumin (PV) expressing cells.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work has elucidated potential mechanisms by which PNNs are degraded in response to altered experience and neuropsychiatric conditions. For example, microglia have been implicated in PNN structural development and degradation ( Crapser et al, 2020a , b ; Nguyen et al, 2020 ). Further, sex differences have been observed in the neuroimmune response to stress ( Fonken et al, 2018 ; Gildawie et al, 2020b ), suggesting a microglia-mediated mechanism may underlie differences between males and females in their behavioral and neural response to repeated adversity during sensitive periods of development.…”
Section: Discussionmentioning
confidence: 99%
“…Two hallmarks of AD are extraneuronal deposition of the amyloid-beta protein in the form of plaques and intraneuronal aggregation of the microtubule-associated protein tau in the form of filaments [ 227 , 228 ]. Some studies document a partial loss of CS-GAGs/CSPGs in the PNNs of patients and mouse models of AD, particularly in the cingulate, frontal, temporal, and entorhinal cortexes [ 224 , 229 , 230 ] and middle frontal gyrus [ 231 ] in humans, and in the hippocampus CA1, CA2, and CA3 [ 232 ], subiculum, and visual cortex [ 231 ] in mice. However, other studies report no alteration of PNNs in the brains of AD patients or mice in the human insular cortex and subcortical regions [ 233 ]; human primary sensory, secondary, and associative areas of the temporal and occipital lobe [ 234 ]; mouse parietal cortex [ 233 ].…”
Section: Pnns and Memory-related Diseasesmentioning
confidence: 99%
“…However, other studies report no alteration of PNNs in the brains of AD patients or mice in the human insular cortex and subcortical regions [ 233 ]; human primary sensory, secondary, and associative areas of the temporal and occipital lobe [ 234 ]; mouse parietal cortex [ 233 ]. A recent study pointed to an intriguing role of microglia activation, triggered by amyloid plaques, in mediating extensive PNN loss in a mouse model of AD [ 231 ]. While there are no studies reporting a PNN increase in human AD brains, mice characterized by amyloid-beta plaque production (APP/PS1 mice) show increased WFA labeling around hippocampal PV neurons and the upregulation of several ECM proteins in hippocampal synaptosome preparations at early stages (3 months of age), when amyloid-beta plaques are not yet observed, but when contextual fear memory is impaired and long-term potentiation (LTP) is reduced.…”
Section: Pnns and Memory-related Diseasesmentioning
confidence: 99%